First-Line Tyrosine Kinase Inhibitors Combined With Local Consolidative Radiation Therapy for Elderly Patients With Oligometastatic Non-Small Cell Lung Cancer Harboring EGFR Activating Mutations - Hu, Xiaolong; Li, Hongqi; Kang, Xiaoli; Wang, Xuan; Pang, Haifeng; Liu, Chen; Zhang, Jianchun; Wang, Yingjie (Frontiers in Oncology, 2022)
Background: The aim of this study was to investigate the efficacy and safety of combined application of local consolidative radiation therapy (LCRT) and first-line tyrosine kinase inhibitors (TKIs) for the treatment of primary tumors and all oligometastatic sites in oligometastatic NSCLC harboring Epidermal Growth Factor Receptor (EGFR) activating. Patients and Methods: Elderly patients with oligometastatic NSCLC (≤5 metastases) harboring EGFR activating at the time of diagnosis were identified. The patients treated with first-line TKIs alone or in combination with LCRT. Progression‐free survival (PFS) and overall survival (OS) were estimated based on the Kaplan-Meier method. Results: A total of 122 elderly patients were enrolled between February 2010 and January 2018. Among them, 41.0% (n=50) received TKIs combined with LCRT (TKIs+LCRT group), whereas 59.0% (n=72) received TKIs monotherapy (TKIs alone group). The patients were followed up for a median length of 34 months (ranging from 7.0 months to 64 months). The median PFS in TKIs+LCRT group was 17 months (95%CI: 15.37-18.63), which was significantly longer than that of TKIs-alone group (12 months; 95%CI: 11.05-12.95)(p＜0.001). The median OS in TKIs+LCRT group was 38 months (95%CI: 35.61-40.39), while that of TKIs-alone group was 29 months (95%CI: 26.86-31.14) (p＜0.001). Results of multivariate analyses suggested that LCRT, one to two metastases, and good ECOG PS were independent factors predicting better PFS (p＜0.001, p=0.004, and p=0.027). Moreover, LCRT, good ECOG PS, and T1-2 stage were independent factors predicting better OS (p＜0.001, p=0.007 and p=0.007). Most of the patients suffered from grade 1 to 2 toxicities, and no treatment-related death was recorded. Conclusion: The results of this investigation show that first-line TKIs combined with LCRT may improve the survival of elderly patients with oligometastatic NSCLC harboring EGFR activating without causing much toxicity. This approach may be therefore be applied in the treatment of elderly patients with oligometastatic disease.